NF2 alteration in mesothelioma - Sekido, Yoshitaka; Sato, Tatsuhiro (Frontiers in Toxicology, 2023)
The NF2 tumor suppressor gene is a frequent somatically mutated genes in mesothelioma, with 30–40% mesotheliomas showing NF2 inactivation. NF2 encodes merlin, a member of the ezrin, radixin, and moesin (ERM) family of proteins that regulate cytoskeleton and cell signaling. Recent genome analysis revealed that NF2 alteration may be a late event in mesothelioma development, suggesting that NF2 mutation confers a more aggressive phenotype to mesothelioma cells and may not be directly caused by asbestos exposure. The Hippo tumor-suppressive and mTOR pro-oncogenic signaling pathways are crucial cell-signaling cascades regulated by merlin. Although the exact role and timing of NF2 inactivation in mesothelioma cells remain to be elucidated, targeting the NF2/merlin-Hippo pathway may be a new therapeutic strategy for patients with mesothelioma.